RICHTMYER-MESHKOV-TYPE INSTABILITY OF A CURRENT SHEET IN A RELATIVISTICALLY MAGNETIZED PLASMA - Inoue, Tsuyoshi (The Astrophysical journal, 2012)
The linear stability of a current sheet that is subject to an impulsive acceleration due to shock passage with the effect of a guide magnetic field is studied. We find that a current sheet embedded in relativistically magnetized plasma always shows a Richtmyer-Meshkov-type instability, while the stability depends on the density structure in the Newtonian limit. The growth of the instability is expected to generate turbulence around the current sheet, which can induce the so-called turbulent reconnection, the rate of which is essentially free from plasma resistivity. Thus, the instability can be applied as a triggering mechanism for rapid magnetic energy release in a variety of high-energy astrophysical phenomena such as pulsar wind nebulae, gamma-ray bursts, and active galactic nuclei, where the shock wave is thought to play a crucial role.